Report about the 1st De Frutos - Universidad Miguel Hernández Judo Scientific Congress with Training Camp - Pulido González, Juan José (Revista de Artes Marciales Asiáticas, 2013)
The current report resumes the 1st De Frutos-Universidad Miguel Hernández Judo Scientific Congress, held in San Juan de Alicante (Spain) from the 27th to the 30th of June in 2013. Three plenary sessions in classroom, 12 oral communications, a round – table, 2 theoretical – practical workshops on tatami, and 3 randori sessions were developed. This congress was a new event where judo personalities at the international level as well as scientists from the whole Spanish geography interested in this field assisted. The event complied the aim to approach the science to judo professionals and vice versa. A total amount of 112 participants were in the congress.